Postural control exercise without using the upper limbs improves activities of daily living in patients with stroke - Kamijo, Akio; Furihata, Chisato; Kimura, Yuki; Furuhata, Isamu; Ohtani, Takeshi; Miyajima, Takeshi (Frontiers in Rehabilitation Sciences, 2023)
Stroke is one of the most common neurological disorders worldwide. Stroke survivors have restricted activities of daily living (ADL) and lower functional independence measures (FIM) after disease onset. Recovery of postural control abilities in patients with stroke is one of the most important therapeutic goals. In this study, we examined the differences in the FIM motor items between groups that performed postural control exercises with the upper limb and those that performed postural control exercises without the upper limb. The medical records of patients with stroke admitted and discharged from the Recovery Rehabilitation Unit at Azumino Red Cross Hospital between 2016 and 2018 were reviewed. We retrospectively investigated the relationships between postural control exercises with or without upper limbs, FIM motor items at admission and discharge, and percentage of gait acquisition at discharge. Among the thirteen FIM motor items, nine (bathing, dressing the upper body, dressing the lower body, toileting, transfers [bed, chair, and wheelchair], transfers [toilet], transfers [tub or shower], locomotion, and climbing of stairs) were significantly different between the two groups (those who performed postural control exercises with the upper limb and those who performed postural control exercises without the upper limb). Patients with stroke who performed postural control exercises without the upper limbs showed a higher percentage of gait acquisition. Touch contact during quiet standing reduces body sway and the associated fluctuations. However, continual practice of postural control with a small degree of body sway for a long period after a stroke would result in decreased pressure on the sole. This may hinder postural control relearning. Touch contact also reduces anticipatory postural adjustment, which may limit the improvement in balance ability during physical exercise. Postural control exercises without the upper limbs improve postural control ability and may be beneficial from a long-term perspective.